The Clinical Characteristics of Endometrial Cancer With Extraperitoneal Metastasis and the Value of Surgery in Treatment. (27th July 2020) - Guo, Jianbin; Cui, Xiujuan; Zhang, Xindong; Qian, Haili; Duan, Hua; Zhang, Ying
Objective: To describe the clinical and pathological features of endometrial carcinoma with extraperitoneal metastasis and examine whether surgery could improve the prognosis. Methods: The Surveillance, Epidemiology, and End Results database was used to analyze 730 patients who were diagnosed with extraperitoneal metastasis of endometrial cancer from 2010 to 2015, including metastasis to the lung, bone, or brain. Results: Of the 730 patients, 372 (50.96%) patients had single lung metastases, and 196(26.85%) patients had multiple organ metastases that included pulmonary invasion. Therefore, the lung was the most common target organ for extraperitoneal metastasis of endometrial cancer. In multivariate risk factor analysis, grade 3 tumor (odds ratio = 3.39, P < .001), positive peritoneal cytology (odds ratio = 2.02, P < .001), and cervical stromal invasion (odds ratio = 1.42, P = .030) were independent risk factors for extraperitoneal metastasis. Once metastasis occurred in the brain or multiple organs, the prognosis was often poor. Of the patients, 362 underwent surgery, and surgery was performed only for primary tumors of the reproductive organs in almost all patients (97.23%) with extraperitoneal metastasis. The median cancer-specific survival periods of patients with solitary pulmonary metastasis undergoing surgery and those without surgery were 23 (16.43-29.57) months and 9 (6.21-11.79) months, respectively ( P < .001), and survival superiority also existed in patients with bone metastasis (19 vs 8 months, P = .015) and multiple organs metastases (15 vs 4 months, P < .001). However, patients with brain metastasis had the same median survival period in the 2 groups (6 months, P = .146). Conclusions: The lung was the most common target organ for extraperitoneal metastasis in patients with endometrial cancer. Surgery was associated with improved survival in women with extraperitoneal metastasis, except for patients with brain metastasis.